EFFICIENT AND ROBUST VESSEL DETECTION SYSTEM - ABDUL MANAB, MUHAMMAD ZHARIF (Universiti Teknologi PETRONAS, 2016)
A proposition of method for envisioning the depth and thickness of a blood vessel in hypodermis layer in the human skin by applying an algorithm to analyze the diffuse reflectance images at three isosbestic wavelengths: 420, 585, and 800 nm. Monte Carlo and Monte Carlo Multi-Layer simulation clearly presented a relation among optical densities, depth, and thickness of the blood vessel region under specifies concentrations of melanin in the epidermis layer and blood in dermis layer. Experiments with additional extension of an array of LEDs surrounding the CCD camera indicate that if there is no obstruction of the three isosbestic wavelength such as foreign light ray from surrounding area, the focused circular blood region can be visualized with errors of 2% for the depth and 9% for the thickness to the given values. Arrangement of the arrays of LEDs are calculated and placed in a certain degree to form a circle to ensure homogenous light ray been propagate onto the human skin.